2017
DOI: 10.3390/polym9100478
|View full text |Cite
|
Sign up to set email alerts
|

Supported Ionic Liquid Silica as Curing Agent for Epoxy Composites with Improved Mechanical and Thermal Properties

Abstract: Abstract:The present study aims to improve the mechanical properties of epoxy composite by incorporating supported ionic liquid silica (IL-silica). The IL-silica not only showed improved interfacial interaction and reinforcement, but also served as cure agent of epoxy composites. The differential scanning calorimetry analysis revealed that epoxy composites could be successfully cured with IL-silica without any routine curing agents. IL-silica/epoxy composites presented higher mechanical and thermal properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
3
14
0
Order By: Relevance
“…In particular, the migrations of silica and curatives play a vital role in the vulcanizates, which would deteriorate the mechanical, thermal and rheological properties during service. To attain good property stability, the filler–rubber interfacial interactions should be mediated crucially [ 49 , 51 ] while the general methodologies for the industry are not successful until the usage of ILs [ 43 ]. Figure 3 shows photographs of the compounds and vulcanizates after being stored at room temperature for one year.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the migrations of silica and curatives play a vital role in the vulcanizates, which would deteriorate the mechanical, thermal and rheological properties during service. To attain good property stability, the filler–rubber interfacial interactions should be mediated crucially [ 49 , 51 ] while the general methodologies for the industry are not successful until the usage of ILs [ 43 ]. Figure 3 shows photographs of the compounds and vulcanizates after being stored at room temperature for one year.…”
Section: Resultsmentioning
confidence: 99%
“…The ATR-FTIR spectra of the MP, MP-SilPrCl, and MP-SilPrMImCl supports are very similar, showing that the chemical integrity of the matrix is maintained. Moreover, an additional band at 1571 cm −1 is observed in the MP-SilPrMImCl spectrum, being attributed to the stretching vibrations of the imidazole ring skeleton [ 39 , 40 ], which therefore reinforces the success of the immobilization process.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, tailoring the balance of interactions between the polymer medium, the O/I nanoparticles and the POSS®-POSS® interaction (leading to the formation of microsize aggregates) is a key issue for designing proper inorganic-rich nanostructures required for enhancements of mechanical properties [29][30][31][32][33][34][35][36] in addition to fire resistance. Recently, several groups reported significant advantages of using ionic liquids (ILs) as dispersing agents for epoxy matrices reinforced with silica nanoparticles [37,38]. These authors have shown that the introduction of ILs based on imidazolium-based cations was a promising strategy for tailoring nanocomposite morphology at the nanoscale [37,38].…”
Section: Epoxy Network Synthesismentioning
confidence: 99%
“…Recently, several groups reported significant advantages of using ionic liquids (ILs) as dispersing agents for epoxy matrices reinforced with silica nanoparticles [37,38]. These authors have shown that the introduction of ILs based on imidazolium-based cations was a promising strategy for tailoring nanocomposite morphology at the nanoscale [37,38].…”
Section: Epoxy Network Synthesismentioning
confidence: 99%